Vertiginous epilepsy in the pediatric population - Wood, Alexandra M.; Thompson-Harvey, Adam; Kesser, Bradley W. (Frontiers in Neurology, 2024)
Vertiginous epilepsy (VE) is a rare and underrecognized epilepsy subtype in the pediatric population. Vertiginous symptoms are the sole or predominant feature, arise from the vestibular cortex, and seizures are usually brief. The incidence is estimated to be between six and 15 percent of pediatric patients presenting with dizziness. Diagnosis is often delayed for many years following the onset of symptoms, as there are no widely accepted diagnostic criteria. Diagnostic work-up should include a detailed history, physical exam, EEG, and brain imaging with MRI. Vestibular testing is helpful if peripheral vestibulopathy is suspected. Vertiginous epilepsy can have many possible causes, but a large majority are idiopathic or suspected to be genetic. Most patients with vertiginous epilepsy achieve seizure freedom with anti-seizure medications.